The Performance of the PHQ-2 and the Examination of Risks Associated With Postdeployment Depression in Air Force Medical Service Personnel. Issue 6 (25th September 2017) - Tvaryanas, Anthony P.; Maupin, Genny M.; White, Edward D.; Schroeder, Valarie M.; Mahaney, Heather J.
Abstract : This study assessed the performance of the 2-item Patient Health Questionnaire (PHQ-2) in identifying postdeployment depressive disorders in a cohort of Air Force Medical Services personnel ( N = 18, 398). The prevalence of depressive disorders in the cohort was 9.00% based on medical record data. The area under the receiver operating characteristic curve was 0.56, indicating very poor classification accuracy. Sensitivity was 15.53%, specificity was 95.57%, positive predictive value was 25.75%, and negative predictive value was 91.97%. The positive and negative likelihood ratios were 3.51 and 0.88, respectively. Several risk factors associated with postdeployment depressive disorders were identified that could potentially improve screening in this population. What is the public significance of this article?: This study determined classification accuracy of a depressive disorder using the 2-item Patient Health Questionnaire (PHQ-2) in a population of postdeployed Air Force medical service personnel to be low. Inclusion of additional factors including career field and gender slightly improved the diagnostic accuracy. Better identification of depressive disorders in medical personnel is needed in an effort to support those military members who support others.